2017
DOI: 10.1371/journal.pone.0169510
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic Recursion Facilitates and Working Memory Predicts Recursive Theory of Mind

Abstract: In this study, we focus on the possible roles of second-order syntactic recursion and working memory in terms of simple and complex span tasks in the development of second-order false belief reasoning. We tested 89 Turkish children in two age groups, one younger (4;6–6;5 years) and one older (6;7–8;10 years). Although second-order syntactic recursion is significantly correlated with the second-order false belief task, results of ordinal logistic regressions revealed that the main predictor of second-order fals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 62 publications
3
31
0
1
Order By: Relevance
“…One potential source is suggested by recent work on working memory and its interaction with the development of recursion in the thought domain. The research question examined in Arslan et al (2017) is strikingly similar to ours, although it targets a different domain: "Why do children need some years to pass second-order false belief tasks once they are able to pass first-order false belief?" (p. 2).…”
Section: Discussionmentioning
confidence: 87%
“…One potential source is suggested by recent work on working memory and its interaction with the development of recursion in the thought domain. The research question examined in Arslan et al (2017) is strikingly similar to ours, although it targets a different domain: "Why do children need some years to pass second-order false belief tasks once they are able to pass first-order false belief?" (p. 2).…”
Section: Discussionmentioning
confidence: 87%
“… According to the paper by van de Pol et al. (), “Higher‐order thinking could still be a source of difficulty for performing theory of mind for other reasons than computational complexity (e.g., due to limited working‐memory).” In this connection we remark that working memory has been shown to play a significant role in higher‐order false belief reasoning (cf.Arslan, Hohenberger, & Verbrugge, ); and also our own work: (Polyanskaya, Braüner, & Blackburn, ). …”
mentioning
confidence: 80%
“…The relation between evaluative complexity and ToM has also been PLOS ONE studied on the level of second-order ToM. Developmental studies indicated that second-order ToM reasoning develops around age 5 or 6 [22,23,33]. Findings on ToM and its relation to evaluative devices were contradictory, though.…”
Section: Social Cognitive and Linguistic Processes Underlying Narratmentioning
confidence: 99%
“…The experimenter presented the 2nd order false-belief question ('Where does his sister think that the boy will look for the chocolate?'). The second story, the birthday present story, was adapted from Sullivan et al's [23] set of stories to Turkish by Arslan et al [33]. Participants' responses were evaluated separately for each story.…”
Section: Plos Onementioning
confidence: 99%